Brønsted acid-catalyzed cycloisomerization of but-2-yne-1,4-diols with or without 1,3-dicarbonyl compounds to tri- and tetrasubstituted furans - Mothe, Srinivasa Reddy (2013)
A Brønsted acid-catalyzed method to prepare tri- and tetrasubstituted furans efficiently from cycloisomerization of but-2-yne-1,4-diols with or without 1,3-dicarbonyl compounds is described. By taking advantage of the orthogonal modes of reactivity of the alcoholic substrate through slight modification of the reaction conditions, a divergence in product selectivity was observed. At room temperature, p-TsOH·H2O-mediated tandem alkylation/cycloisomerization of the propargylic 1,4-diol with the β-dicarbonyl compound was found to selectively occur to provide the tetrasubstituted furan product. On the other hand, increasing the reaction temperature to 80 °C was discovered to result in preferential p-TsOH·H2O-catalyzed dehydrative rearrangement of the unsaturated alcohol and formation of the 2,3,5-trisubstituted furan adduct.